سياسة الشيخ قاسم بن محمد آل ثاني في الحكم 1878- 1913 م - القحطاني، عبدالقادر بن حمود عبدالعزيز (المركز الجامعي أمين العقال الحاج موسى أق أخموك لتامنغست - معهد الحقوق والعلوم السياسية, 2018)
Birth and Early Life: There is no collective agreement among historians on his birth, he was born between (1798 - 1826). He grew up in his father's house in an environment of literature, ethics and religion. He was educated by the scholars of his time mainly in religion, literature, politics and other sciences, and thus, became a jurisprudent in religion and a scholar in Arabic language and as such became qualified to be an eloquent preacher, a fair judge, and poet of glory. Sheikh Qasem bin Mohammed was one of the leading merchants of pearls in the Arabian Gulf. This trade had generated him large amounts of money. He had been known for his generosity and charity for the good. He helped the needy and spent a lot of money on science students and Imams, building mosques and Koranic schools. In addition, he funded publishing of selected Islamic books and distributed them among Muslims inside and outside Qatar. In politics, he became the de facto ruler of the country in 1989 due to his father's age. Following the death of his father, Sheikh Mohammed bin Thani, on December 18, 1878, he took over power and continued to rule until his death on 17 July 1913. Sheikh Qasem adopted a wise policy at the local and foreign levels. At the local level, he worked to unite tribes and groups of people under his rule through a policy based on justice and equality among citizens in rights and duties. On the external or international level, he tried not to interfere in the affairs of others and not to allow interference in his country's internal affairs. Sheikh Qasem preferred the alliance with the Ottoman Empire and the use of its forces to defend his country against any threat, and therefore, allowed the entry of Ottoman forces into the country in 1871. The Ottoman forces had remained in the Country until Sheikh Qasem’s death. These forces left Qatar during the reign of Sheikh Abdullah bin Qasem in 1915, due to the British pressure on the Ottomans in the First World War. Sheikh Qasem's rejection of British protection and his preference for Ottoman protection was one of the reasons that made Britain create border problems with his neighbors, especially with Bahrain, Abu Dhabi and Saudi Arabia. But with the help of God, his strong personality, and his people’s support he had been able to confront and defeat those challenges. Sheikh Qasem, despite his acceptance of the Ottoman alliance, he did not allow the Ottomans to interfere in the affairs of the Country. When the Ottomans tried to intervene in the affairs of the Country, he fought and defeated them in 1893, in a battle known as “Al Wajba”. Sheikh Qasem had maintained and protected his country's independence and sovereignty, and as such, he deserved to be considered the founder of the State of Qatar in modem history. So, the date of his assumption of power on December 18 has become Qatar’s National Day celebrated by the State, government and people.
ولادته ونشأته: ليس هناك اتفاق جماعي بين المؤرخين بشأن ولادته، فهو ولد بين (1798 – 1826م). نشأ في بيت والده على الأدب والأخلاق والدين، وتلقى تعليمه على أيدي علماء عصره في الدين والأدب والسياسة وغيرها من العلوم، وبذلك أصبح فقيها في الدين وأديبا باللغة العربية أهلته أن يكون خطيبا مفوها وقاضيا عادلا وشاعرا مجيدا. الشيخ قاسم بن محمد كان من كبار تجار اللؤلؤ في الخليج العربي، وقد درت عليه هذه التجارة أموالا طائلة، وقد عرف عنه بكرمه وحبه للخير فكان يساعد المحتاجين، وينفق على طلبة العلم وعلى أئمة المساجد وبناء المساجد ومدارس تحفيظ القران الكريم، كذلك طبع الكتب الإسلامية وتوزيعها على المسلمين داخل قطر وخارجها. وفي المجال السياسي: أصبح منذ سنة 1869، بمثابة الحاكم الفعلي للبلاد نظرا لكبر سن والده. وعقب وفاة والده الشيخ محمد بن ثاني في 18 ديسمبر 1878 م تسلم الحكم من بعده، واستمر في الحكم حتى تاريخ وفاته في 17 يوليو 1913م. انتهج الشيخ قاسم في الحكم سياسة حكيمة على المستوى المحلي وعلى المستوى الخارجي، فعلى المستوى المحلي، عمل على توحيد القبائل وفئات الشعب تحت حكمه من خلال سياسة تقوم على العدل والمساواة بين المواطنين في الحقوق والواجبات. أما على المستوى الخارجي أو الدولي، فقد حاول عدم التدخل في شؤون الآخرين وعدم السماح بالتدخل في شؤون بلاده الداخلية. الشيخ قاسم فضل التحالف مع الدولة العثمانية والاستعانة بقواتها في الدفاع عن بلاده ضد أي تهديد، ولذلك سمح بدخول القوات العثمانية البلاد سنة 1871م، وبقيت القوات العثمانية في البلاد حتى تاريخ وفاته ولم تخرج من البلاد إلا في عهد خلفه الشيخ عبد الله بن قاسم في سنة 1915م، نتيجة الضغط البريطاني على العثمانيين في الحرب العالمية الأولى. كان نتيجة رفض الشيخ قاسم الحماية البريطانية وتفضيله الحماية العثمانية من الأسباب التي جعلت بريطانيا تخلق له مشاكل حدود مع جيرانه وبالذات مع البحرين وأبو ظبي والسعودية، ولكن بعون من الله وقوة شخصيته والتفاف شعبه من حوله تمكن من مواجهة تلك التحديات وينتصر عليها. الشيخ قاسم على الرغم من قبوله التحالف العثماني غير أنه لم يسمح للعثمانيين التدخل في شؤن البلاد التي هي من مسؤوليته، لذلك حينما حاول العثمانيون التدخل في شؤون البلاد حاريهم وانتصر عليهم سنة 1893 م، والمعروفة بمعركة الوجبة. وبسبب محافظته على استقلال وسيادة بلاده استحق أن يقال عنه المؤسس لدولة قطر في التاريخ الحديث وأن يصبح تاريخ توليه الحكم في: 18 ديسمبر يوماً وطنياً تحتفل فيه الدولة حكومة وشعباً.
Keywords: الحكم الملكي -- دول مجلس التعاون الخليجي -- قطر -- المجتمع القطري -- الشيخ محمد بن قاسم آل ثاني ، ملك قطر السابق -- السياسة الخارجية -- العلاقات الدبلوماسية -- السياسة الإستعمارية -- مستخلصات الأبحاث -- الترجمة